Presence of Hepatitis B virus DNA in follicular fluid in female Hepatitis B carriers and outcome of IVF/ICSI treatment: A prospective observational study. (August 2019) - Mak, Jennifer S.M.; Leung, Maran B.W.; Chung, Cathy H.S.; Chung, Jacqueline P.W.; Cheung, L.P.; Lao, Terence T; Li, T.C.
Abstract: Objective: To determine the relationship between the presence of detectable HBV DNA in the follicular fluid in HBV carriers with IVF/ICSI treatment outcome. Study design: A prospective observational study conducted in the Assisted Reproductive Unit, a tertiary referral centre affiliated with the Department of Obstetrics and Gynecology, The Chinese University of Hong Kong; and the Union Reproductive Medicine Centre at Union Hospital, Hong Kong. The primary outcome measure was pregnancy rate. Secondary outcome measures were the prevalence of detectable HBV DNA in the follicular fluid, implantation rate, clinical pregnancy rate, ongoing pregnancy rate and live birth rate. Results: HBV DNA was detected in the follicular fluid of 28 (43.8%) of the 64 women, and the mean level in this group in log10 copies/mL (±SD) was 4.36 ± 1.85. Women with detectable follicular fluid HBV DNA were younger, lighter, had longer duration of infertility, higher incidence of detectable serum HBV DNA (OR 4.592, 95% C I 2.333–9.038), and significantly wider range in the number of total fertilized, viable embryos, and blastocyst rate, but no difference in cycle characteristics, stimulation and pregnancy outcomes, although the almost doubled ongoing pregnancy/live birth rate per cycle initiated (60.7% versus 38.9%) failed to reach statistical significance due to the small numbers. Conclusion: Our results suggested HBV infection did not appear to be detrimental to the outcome of IVF/ICSI treatment.